Understanding the mechanisms of groundwater recharge and flow in periglacial environments: new insights from the Ledo-Paniselian aquifer in Belgium - Walraevens, Kristine; Fernández-Lagunas, Albert; Blaser, Petra; Aeschbach, Werner; Vandenbohede, Alexander; Van Camp, Marc (Journal of contaminant hydrology, 2021)
The Ledo-Paniselian aquifer in Belgium has been proposed to offer unique opportunities to study groundwater recharge and flow in periglacial conditions during the Last Glacial Maximum (LGM), due to its location in the permanent permafrost area, south of the ice sheet at that time. A palaeoclimatic record had been set up previously for this aquifer, consisting of major ion chemistry, stable isotopes, radiocarbon and noble gases. In this paper, methane data have been used to further refine the paleoclimatic model, along with revisiting in detail the set of chemical data, focusing on the area where groundwaters, recharged around the LGM, are known to occur. It was found that the high methane concentrations corroborate the hypothesis of groundwater recharge taking place during permafrost melting, from methane-bubbling lakes that had developed to the south of an eolian sand ridge. A relict flow path, existing in the aquifer during some period as permafrost was thawing, has been established, starting from these temporary recharge areas, based on various chemical parameters, radiocarbon model ages and noble gas recharge temperatures.